Smartphone Addiction Among Undergraduates in Lagos State, Nigeria - Biobaku, Muftau Olanrewaju; Adisa, Abayomi Bamidele (European Scientific Journal, ESJ, 2026)
Smartphone use has significant implications for the mental health of youth, particularly undergraduates who perceive it as an integral part of their identity and social lives. Although previous studies have examined the effects of smartphones globally, limited attention has been given to undergraduates in Lagos State. This study investigates the level of addiction to smartphones and as a mental health indicator among undergraduates in Lagos State, Nigeria. Anchored on the Problematic Internet Use Model, the study employed a survey research method. The population comprised undergraduates from public and private universities in Lagos State, Nigeria. Multistage sampling procedure was adopted: first, universities in Lagos State were stratified into public and private; second, simple random technique enhanced the selection of three each of public and private universities out of a total of four public and five private universities; third, disproportionate sampling approach guided the allotment of 105 respondents each to the six selected universities where a total of 630 undergraduates aged 20–40 participated; and forth, convenience sampling was employed to enumerate the specific respondents. The study employed a self-developed Smartphone Addiction Questionnaire (SAQ), which contains demographics and 12 closed-ended items to elicit data from the undergraduates. The questionnaire was validated by reviews from two scholars, each from the fields of Communication and Media Studies and Test and Measurement, who reviewed the instrument on face value. Subsequently, a reliability test was conducted among 60 undergraduates who were subsets of the population but not part of the sampled universities for the main study. The findings were analysed using Cronbach’s alpha coefficient, which yielded 0.84, indicating acceptable reliability for the study. The survey was carried out online using Google Forms over a period of four months, from June to October 2025, when the undergraduates were on holiday. Ethically, the study was carried out among adults whose consent was sought and secured before the study was conducted. There was also strict adherence to anonymity and confidentiality clauses. Descriptive statistics were applied. Results revealed that 76.8% of respondents were female, and 58.4% spent more than six hours daily on their smartphones. There is a moderate level of smartphone addiction among undergraduates in Lagos State, Nigeria (M = 2.940, SD = 1.120), manifesting in a habitual and compulsive usage pattern without widespread severe impairment. There is a need for preventive interventions on compulsive smartphone checking and anxiety-related dependence to avoid undergraduates skidding into severe addictions.